Comprehensive Analysis of the Complete Mitochondrial Genome of Paeonia ludlowii Reveals a Dual-Circular Structure and Extensive Inter-Organellar Gene Transfer - Zhefei Zeng; Zhengyan Zhang; Ngawang Norbu; Ngawang Bonjor; Xin Tan; Shutong Zhang; Norzin Tso; Junwei Wang; La Qiong (Biology, 2025)
Paeonia ludlowii, a critically endangered species endemic to Tibet, China, possesses significant ornamental, culinary, and medicinal value. However, its mitochondrial genome remains understudied, limiting insights into its evolutionary mechanisms and constraining conservation genetics applications and molecular breeding programs. We present the first complete assembly and comprehensive analysis of the P. ludlowii mitochondrial genome. Most remarkably, we discovered that the P. ludlowii mitogenome exhibits an atypical dual-circular structure, representing the first documented occurrence of this architectural feature within the genus Paeonia. The assembled genome spans 314,371 bp and encodes 42 tRNA genes, 3 rRNA genes, and 31 protein-coding genes, with a pronounced adenine–thymine bias. This multipartite genome structure is characterized by abundant repetitive elements (112 functionally annotated SSRs, 33 tandem repeats, and 945 dispersed repeats), which potentially drive genome rearrangements and facilitate adaptive evolution. Analyses of codon usage bias and nucleotide diversity revealed highly conserved gene expression regulation with limited variability. Phylogenetic reconstruction confirms that P. ludlowii, P. suffruticosa, and P. lactiflora form a monophyletic clade, reflecting close evolutionary relationships, while extensive syntenic collinearity with other Paeonia species underscores mitochondrial genome conservation at the genus level. Extensive inter-organellar gene transfer events, particularly from chloroplast to mitochondrion, suggest that such DNA exchanges enhance genetic diversity and promote environmental adaptation. The discovery of the dual-circular architecture provides novel insights into plant mitochondrial genome evolution and structural plasticity. This study elucidates the unique structural characteristics of the P. ludlowii mitochondrial genome and establishes a crucial genetic foundation for developing targeted conservation strategies and facilitating molecular-assisted breeding programs for this endangered species.